Do trabalho no tráfico de drogas ao ofício de florista: um estudo de psicologia do trabalho em situações marginais - Aiezha Flavia Pinto Guabiraba (2017)
In view of the social and historical context in which the teenager and the poor and black young people are the social enemy to be persecuted, the public politics of a criminal state are carried out in the sense of punishment, instead of strengthening the protection and guarantee of human rights. This research has sought to elucidate how this situation has brought serious and damaging social consequences related to the punitive ideological strengthening, the extermination of poor youth and repressive and imprisoning policies. We started from the theoretical perspective of Critical Criminology as an analytical tool to understand the criminalization of drug traffickers in a dialogue with Labor Psychology to understand the world of precarious work today, where drug trafficking retailer figures with highlighted as an economic activity that allows for inclusion, even if marginal. We also started from theoretical discussions that have in their center the criminalization directly related to the place that occupies in the social division of labor. We show normative and legal discourses of the hegemonic media, of common sense, of psychological knowledge that, above all, function as knowledge at the disposal of a punitive power that strengthens the stigmas about these young people. The objective of the research was to understand the work´s trajectory of a young person criminalized by the Criminal State. In a qualitative approach, the research was based on the biographical method, based on narrative interviews. This tool privileged, in a psychosociological perspective, the access to the life trajectory of the participant, who, throughout the field research, reported his work course. He narrated in depth his activity in drug trafficking and his profession as a florist, going through the work done during the sentence of provision of community services. The results obtained showed that the work, whether in marginal, illegal and informal activities or in those circumscribed to legality, formal and regulated, is a space of construction of identity, recognition and value, being able to have multiple valences regarding the construction of the persons, depending on the concrete possibilities encountered and the possible senses of being produced, within a unique scope of each experience. We come to the realization that drug trafficking retailing is fundamentally based on the work of children and young adolescents, implying risk, violence and death for this population, so that exploitation of labor appears as an urgency to be overcome. When work is used as a form of penalization and punishment, such as the placement of young people in activities that are not valued enough on the sentence of provision of community services to the community, their potential to promote human development is compromised, resulting in psychosocial repercussions related to shame and humiliation, demarcating that the place in the productive world reserved for these young people is the invisible and devalued work, reinforcing its marginal character. We conclude that formal work, as a right, can enable an identity and psychosocial change andcrossing, favoring the construction of an identity clothed in value, but that the professional way should not be the only way to overcome the situation of labor exploitation of children and adolescent youth in drug trafficking, but rather the guarantee and access to human rights in a broad way